1996
DOI: 10.1182/blood.v88.11.4259.bloodjournal88114259
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of serum soluble CD23 level in chronic lymphocytic leukemia

Abstract: Prognosis of B-cell chronic lymphocytic leukemia (CLL) is based on clinical staging whose limitation is the failure to assess whether the disease will progress or remain stable in early stage (Binet A, or Rai 0, I, II) patients. We previously reported that soluble CD23 (sCD23), a protein derived from the B-cell membrane CD23 Ag, is selectively elevated in the serum of CLL patients. This prospective study assessed the predictive value of serum sCD23 level measured at study entry on the overall survival of all C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 0 publications
2
41
1
4
Order By: Relevance
“…Furthermore, our results contrast with those dealing with other markers in CLL, e.g. IL‐6, serum β 2 m, CD23, thymydine kinase (TK), where serum levels are elevated in the patient group (24–27). Several epidemiological studies have suggested that high serum levels of IGF‐1 may predispose to some types of cancer such as breast cancer in premenopausal women, colon cancer, and prostate cancer (28–30).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results contrast with those dealing with other markers in CLL, e.g. IL‐6, serum β 2 m, CD23, thymydine kinase (TK), where serum levels are elevated in the patient group (24–27). Several epidemiological studies have suggested that high serum levels of IGF‐1 may predispose to some types of cancer such as breast cancer in premenopausal women, colon cancer, and prostate cancer (28–30).…”
Section: Discussioncontrasting
confidence: 99%
“…To identify patients at higher risk of DP a number of independent prognostic factors, such as LDT, soluble CD23, β 2 m, soluble VEGF and serum TK have been proposed in patients with early CLL (18, 24–27, 32). Immunoglobulin mutational status and CD38 expression can now discern on biological ground different CLL clinical outcomes and expression of ZAP‐70, as detected by flow‐cytometry, correlating with IgV H mutational status, DP and survival (33–37).…”
Section: Discussionmentioning
confidence: 99%
“…Rai et al (3) and Binet et al (4), defines subgroups in which risk increases with stage, they are essentially observational, descriptive tools. Elevated levels of serum proteins, including soluble‐CD23 (5), β 2‐microglobulin (6) and thymidine‐kinase (7), have been associated with poor prognosis, and genetic defects in specific molecular pathways, involving p53 at 17p13, or ATM at 11q22 predict resistance to treatment and shortened survival in CLL (8, 9). A breakthrough in risk‐prediction was the demonstration that absence of somatic hypermutations in the rearranged variable regions of the immunoglobulin heavy chains ( IgV H ) genes of the CLL cells predicts for shortened survival, even within each clinical stage (10, 11).…”
mentioning
confidence: 99%
“…Serum markers, including beta‐2 microglobulin ( β 2 m), lactate dehyrogenase, soluble CD23 and serum thymidine kinase, all have been shown to predict progression and survival. However, their value has been limited either by the lack of a standard assay method, variable cut‐off points between series, or the lack of validation in prospective studies (22, 23).…”
mentioning
confidence: 99%